1996
DOI: 10.1161/01.hyp.28.3.409
|View full text |Cite
|
Sign up to set email alerts
|

A Vascular Modulator, Hepatocyte Growth Factor, Is Associated With Systolic Pressure

Abstract: Endothelial cells are known to secrete various antiproliferative and vasodilating factors, such as nitric oxide and natriuretic peptides. The presence of endothelial dysfunction, well known in hypertensive individuals, potentially results in the development and progression of atherosclerosis. Therefore, it is important to know the factors that might influence endothelial cell growth. We examined the mitogenic actions of hepatocyte growth factor (HGF) on human endothelial and vascular smooth muscle cells. Exoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 41 publications
5
110
4
Order By: Relevance
“…As was expected, administration of perindopril significantly increased local HGF expression associated with the inhibition of neointimal formation. Because HGF is an endotheliumspecific growth factor and thus stimulated growth of endothelial cells, 3,4 increased local HGF production would probably stimulate regeneration of endothelial cells after balloon injury. Of particular interest, vasodilator response of ballooninjured coronary arteries was restored by treatment with perindopril versus vehicle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As was expected, administration of perindopril significantly increased local HGF expression associated with the inhibition of neointimal formation. Because HGF is an endotheliumspecific growth factor and thus stimulated growth of endothelial cells, 3,4 increased local HGF production would probably stimulate regeneration of endothelial cells after balloon injury. Of particular interest, vasodilator response of ballooninjured coronary arteries was restored by treatment with perindopril versus vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of endothelial cells, we hypothesize that rapid regeneration of endothelial cells, not accompanied by growth of vascular smooth muscle cells (VSMC), may have therapeutic potential in abnormal vascular growth, such as neointimal formation after angioplasty. From this viewpoint, we previously reported that hepatocyte growth factor (HGF) has the unique characteristic of stimulating endothelial cell growth exclusively without stimulating VSMC growth, 3,4 although HGF is well known to be a mesenchyme-derived pleiotropic factor that regulates cell growth and motility and morphogenesis of various types of cells. 5,6 Moreover, the presence of HGF and its specific receptor, c-met, has been detected in vascular tissues.…”
mentioning
confidence: 99%
“…7,8 From this viewpoint, hepatocyte growth factor (HGF) originally cloned as hepatocyte mitogen, 9 is also of particular interest, as HGF exclusively stimulated the growth of endothelial cells without replication of vascular smooth muscle cells (VSMC). [10][11][12] Indeed, we and others previously reported that HGF is a potent angiogenic growth factor which is useful for effective therapeutic angiogenesis in a rabbit ischemia model. 13,14 Unexpectedly, the mitogenic activity of HGF is more potent than that of VEGF in human aortic endothelial cells in vitro, as well as a rabbit hindlimb ischemia model in vivo.…”
Section: Introductionmentioning
confidence: 93%
“…The concentration of HGF in the myocardium was determined by the enzyme-immunoassay with an anti-human HGF antibody, as described previously. 11,15 Briefly, a rabbit anti-rat or an anti-human HGF IgG was coated on 96-well plates (Corning, NY, USA) at 4°C for 15 h. After blocking with 3% bovine serum albumin in phosphate-buffered saline (PBS), the conditioned medium was added to each well. Afterwards, the preparation was incubated for 2 h at 25°C.…”
Section: Measurement Of Hgf Concentration In Myocardiummentioning
confidence: 99%
“…Also HGF is considered a humoral mediator of epithelial-mesenchymal interactions respon-sible for morphogenic tissue interactions during the period of embryonic development and organogenesis. 8,9 Recently, HGF has been reported as a mitogen exclusively for endothelial cells without the replication of vascular smooth muscle cells (VSMC), [10][11][12][13] thereby indicating it as a potential angiogenic growth factor. Indeed, activation of the HGF system promoted angiogenesis in a Matrigel system, 14 however, this system provides far from physiological conditions.…”
Section: Introductionmentioning
confidence: 99%